The effectiveness of blog as a social networking site for students / Wan Anisha Wan Mohammad … [et al.] - Wan Mohammad, Wan Anisha (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2010)
Students nowadays are very 'extreme' in communication especially in building networks among themselves. Besides mobile communication, they are also exposed to online communication such as emails, instant messaging and most of all, social networking site such as weblogs. Most of the weblogs are managed by individuals; hence it can establish new type of social relations which develop a social network. Therefore, this research was done since many students choose blogs as a mean to communicate and extend their network. A survey has been done by distributing questionnaires to students from various fields. The results show most of the students think that blogging is effective as through blogs, they can share interests, feelings, experiences and knowledge, keep in touch with old friends and meeting with new friends while only a few of them feels that blog is a healthy hobby and activity. In conclusion, blogging has been identified as an effective social networking site for students.